Competitive Advantage in Rural Tourism: analysis the strategic resources by farm hotels - Alves, Luana de Oliveira; Silva, Luana Alexandre; Salazar, Viviane Santos (Revista Turismo em Análise, 2018)
The possibility of experiencing activities different from the everyday agitation and having a more intimate contact with nature has directed many tourists to the countryside. To exploit this niche market the rural entrepreneur becomes a strategist in search of new business possibilities that meet this demand. In the area of strategic management, one of the issues that has attracted attention from scholars is the reason that allows companies to develop and maintain a competitive advantage over other competitors. Following this reasoning, this work analyzes the farm-hotels from the perspective of RBV (Resource Based View), whose theory considers the internal factors of a company as determinants of its superior performance. The objective of this research is, therefore, to identify and evaluate the strategic resources that support the competitive advantage of farm hotels based on the analysis of two enterprises: one located in the State of Ceará and the other in Pernambuco. It is a research of a descriptive nature that adopted as an instrument of data collection an open questionnaire, in addition to a semi-structured interview to deepen the information obtained. Among the observations made during the study, it was possible to identify that physical resources, such as location, and human resources, especially customer service, can be seen as strategic resources that support the competitive advantage of this type of enterprise.